Thermo-hydro-mechanical process and damage mechanism of a cold-region canal under coupled wetting–drying and freezing–thawing cycles - Li, Shuangyang; Wang, Chong; Yang, Jiale; Lai, Yuanming; Jiang, Qi; Wan, Xusheng (Acta geotechnica, 2022)
In cold regions, periodic wetting–drying and freezing–thawing (WDFT) actions lead to frequent and heavy canal damage, weakening the water-conveyance capacities of canals. The WDFT cycle is a complicated process involving a thermo-hydro-mechanical (THM) interaction. To understand the THM process and damage mechanism of a cold-region canal (CRC), a THM model is proposed and used to simulate a centrifuge test on a CRC. The centrifuge modeling and numerical simulation results show that there are three freezing–thawing processes in the shallow ground of the CRC. Thus, a notable water–ice phase and water redistribution occur in the ground with alternating freezing–thawing process. The drastic heat and water variations of the freezing–thawing ground result in repeated frost deformations and even failure of the CRC. In addition, several possible defects in the centrifuge modeling of the CRC in a coupled WDFT environment are pointed out according to the result comparisons between the centrifuge modeling and numerical simulation. This study can improve the understanding of the THM process and damage mechanism of CRCs in complex environments and is also a reference for further study.